2021
DOI: 10.1007/s40122-021-00246-z
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine Versus Ketorolac as an Adjuvant to Local Wound Infiltration Anesthesia in Open Colorectal Surgery: A Prospective Randomized Controlled Study

Abstract: Introduction: Adding adjuvants to local wound infiltration (LWI) provides long analgesic duration with fewer adverse effects. We aimed to compare the clinical effects of nalbuphine and ketorolac as an adjuvant to LWI in patients undergoing open colorectal cancer surgery. Method: A total of 126 ASA I-III patients aged C 18 years who were scheduled for open colorectal cancer surgery were included. Patients were randomly assigned to receive LWI using 10 mL 0.75% ropivacaine, with 20 mL normal saline (group R), 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Ketolorac was given every 12 h as basic analgesia. Finally, Ren et al reported that ketorolac and nalbuphine associated with ropivacaine by local wound infiltration allowed a reduction in opioid consumption 10 . No basic analgesia was given.…”
Section: Resultsmentioning
confidence: 99%
“…Ketolorac was given every 12 h as basic analgesia. Finally, Ren et al reported that ketorolac and nalbuphine associated with ropivacaine by local wound infiltration allowed a reduction in opioid consumption 10 . No basic analgesia was given.…”
Section: Resultsmentioning
confidence: 99%
“…In cases of open colorectal surgery, WI has been found to be less effective than epidural analgesia in terms of analgesic impact and functional recovery, though it is associated with a lower risk of adverse events such as hypotension [ 110 , 158 ]. Enhancements in the duration and quality of WI analgesia can be achieved by incorporating adjuvants such as nalbuphine or ketorolac [ 159 ]. Notably, while WI carries a risk for wound infection and other potential complications like systemic toxicity from the local anesthetic (particularly if used concurrently with TAP block), or bruising and hematoma from vascular perforation, such incidences are generally rare [ 160 ].…”
Section: Introductionmentioning
confidence: 99%